2002
DOI: 10.1177/000456320203900615
|View full text |Cite
|
Sign up to set email alerts
|

Hyperamylasaemia and Multiple Myeloma

Abstract: This case report describes a 42-year-old Caucasian woman who presented with persistent hyperamylasaemia and no evidence of pancreatic pathology. Further investigations resulted in a diagnosis of light-chain multiple myeloma. Amylase production by epithelial tumours has been well documented but the association with multiple myeloma has only been described in a small number of cases. The link does not appear to be immunoglobulin class-specific but the association with Bence Jones myeloma is unusual. The common f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A common feature of the myeloma cell lines associated with hyperamylasaemia was a translocation of chromosome 1, which harbours the gene for amylase. [7][8][9] Shigemura et al 10 reported that in multiple myeloma with hyperamylasaemia, a majority of cases were due to salivary-type hyperamylasaemia (sialyl salivary-type amylase). In patients with amylase-producing multiple myeloma, the onset of hyperamylasaemia was associated with a rapid disease progression associated with extensive bone destruction and increased mortality.…”
mentioning
confidence: 99%
“…A common feature of the myeloma cell lines associated with hyperamylasaemia was a translocation of chromosome 1, which harbours the gene for amylase. [7][8][9] Shigemura et al 10 reported that in multiple myeloma with hyperamylasaemia, a majority of cases were due to salivary-type hyperamylasaemia (sialyl salivary-type amylase). In patients with amylase-producing multiple myeloma, the onset of hyperamylasaemia was associated with a rapid disease progression associated with extensive bone destruction and increased mortality.…”
mentioning
confidence: 99%
“…As α‐amylases are secreted into the digestive system, small amounts diffuse into the bloodstream and are eliminated through urine and perspiration; so are commonly found in several biological fluids, especially urine, perspiration, and, in addition, in vaginal secretions, breast milk, tear fluid, serum, male and female reproductive tissues, and feces (9–13); however, with the exception of feces, no other body fluid approaches the level of amylases activity in dried stains from the aforementioned biological fluids. In some pathological conditions, especially in pancreatic disorders such as pancreatitis (14) and in several kind of tumors affecting the digestive apparatus (15), the α‐amylase levels may be drastically altered and tissue normally not expressing these enzymes may become relevant sources of α‐amylases (16). α‐amylases are also found in the liver, fallopian tubes, and small intestine; inflammation of these tissues also increases levels.…”
mentioning
confidence: 99%